A culturally relevant education? - Simon Bauer; Tommaso Milani; Kerstin von Brömssen; Andrea Spehar (Educare)
This article contributes to ongoing discussions on education for migrants as a form of integration policy and practice. It does so by investigating whether the initiative Civic Orientation for Newly Arrived Migrants in Sweden constitutes an example of culturally relevant education. Drawing on a mixed-method and multi-level analysis, we hone in on “values” as a discursive construction in order to see how particular principles are linked to Swedishness. Specifically, we show how values are discursively constructed on multiple levels through 1) a qualitative analysis of policy documents instrumental to the implementation of civic orientation; 2) a quantitative corpus-assisted critical discourse analysis of media articles; 3) individual interviews with 14 persons involved in organizing the civic orientation courses; and 4) ethnographic classroom observations from six such courses. Our results show how, on the one hand, Sweden is constructed as the most developed country in the world in terms of values and, on the other hand, migrants are portrayed as antithetical to such an ideal imagination. Furthermore, we show how a specific set of values – human rights and democracy – changes meaning from being universal to becoming particularized and nationalized as “Swedish”.